ASSESSMENT OF MOLECULAR DIVERSITY IN WHEAT (TRITICUM AESTIVUM L. AND TRITICUM DURUM L.) GENOTYPES CULTIVATED IN SEMI-ARID REGION OF GUJARAT - HARSHVARDHAN ZALA; TEJAS BOSAMIA; KALYANI KULKARNI; YOGESH SHUKLA (The Bioscan, 2014)
Molecular diversity was assessed among wheat genotypes cultivated in semi-arid region of Gujarat employing molecular markers. In total, 18 RAPD and eight SSR markers amplified 5554 fragments with 66.83 % polymorphism and 343 fragments with 90.32% polymorphism respectively. Unweighted pair group method with arithmetic mean (UPGMA) analysis generated by RAPD, SSR and combined RAPD and SSR based on genetic distance estimates displayed two major clusters consisting of irrigated aestivum (I), irrigated and rainfed durum (II) wheat genotypes. A Jaccard’s similarity coefficient of all genotypes derived from RAPD data ranged from 0.65 to 0.90 and that of SSR ranged from 0.45 to 0.94. Marker data subjected to analysis of molecular variances revealed more diversity within population. The PIC value for RAPD and SSR markers ranged from 0.91 to 0.96 and 0.57 to 0.76 respectively, with marker indexes of 11.35 and 5.35, demonstrating its utility in genetic diversity analysis. The results of PCoA analysis were comparable to dendrograms. Analysis of molecular variance (AMOVA) for combined RAPD and SSR displayed more variance within and among population than RAPD and SSR. These molecular markers can be put to use for characterization and selection of wheat genotypes suitable for cultivation in irrigated and rainfed conditions.